NATURAL DISASTERS AND PUBLIC CONCERN FOR THEIR CAUSES - Ricardi Adnan; Tuti Budirahayu (Unpad Press, 2023)
This article describes the relationship between natural disasters and community negligence by referring to Jens Beckert's institutional theory (2010). This sociological study has relevance for the general public as well as government agencies. More than two thousand natural disasters occur in Indonesia every year, resulting in more than 10,000 deaths. In some cases, natural disasters are difficult to anticipate by science. However natural disasters caused by human negligence are also not insignificant, such as floods, fires and landslides. In this study, we discuss the community negligence factors that contribute to natural disasters. The study was conducted using the survey method via Google Form to a number of respondents spread across the Jabodetabek area. It also processed secondary data from a number of reports on natural disasters on various social media and digital media. Furthermore, this study shows that a number of disasters caused by human negligence are quite frequent. The facts show that Indonesian people quite often act rashly and without thinking about the long-term impact that their actions will bring. Based on secondary data, this article selects several cases of human negligence that have the potential to cause disaster.